What are the test characteristics of the Waddell incongruency signs for nonorganic back pain?. Issue 5 (May 2017) - Meram, Daniel; White, William
Abstract : EVIDENCE‐BASED ANSWER : The answer is uncertain. Although not directly evaluated for determining organic from nonorganic back pain, the Waddell signs do not seem to be useful for predicting ability or inability to return to work or success of rehabilitation. Additionally, they are only weakly associated with factors such as physical signs, pain, illness behavior, and psychological comorbidities (SOR: B, cohort and cross‐sectional studies)